Letting Go : Feminist and Social Justice Insight and Activism - Valentine, Catherine G.; King, Donna Lee (Book collections on Project MUSE., 2015)
"This book explores alternatives to the contemporary call for individual achievement, accumulation, and attention seeking as the road to happiness and satisfaction in life. And it reveals how the high value placed on radical individualism and competitive striving has devastating personal, social, and environmental consequences"--